2008
DOI: 10.1007/s10038-008-0288-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regulatory polymorphisms in organic ion transporter genes (SLC22A) in the kidney

Abstract: Organic cation transporters (OCTs) and organic anion transporters (OATs) (SLC22A family) play crucial roles in the renal secretion of various drugs. Messengar ribonucleic acid (mRNA) expression of transporters can be a key factor regulating interindividual differences in drug pharmacokinetics. However, the source of variations in mRNA levels of transporters is unclear. In this study, we focused on single nucleotide polymorphisms (SNP) in the promoter region [regulatory SNPs (rSNPs)] as candidates for the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
0
20
1
3
Order By: Relevance
“…Four SNPs (-18C>T, rs3782099, rs1783811 and rs2078267) resulted in moderate decrease of torsemide renal clearance, while the SNP (rs4930423) led to an increased clearance of such drug. Ogasawara et al [57] also discovered one same mutation (-18C>T) from the Japanese cohort, which study concluded that it did not affect the promoter activity or the mRNA expression of this gene. Meanwhile, Lee et al [60] explored the functional consequence of E278K, which mutant possessed a reduced uptake activity of ES, Dehydroepiandrosteon sulfate (DHEA-s) and ochratoxin A (OTA).…”
Section: Oat4mentioning
confidence: 93%
See 2 more Smart Citations
“…Four SNPs (-18C>T, rs3782099, rs1783811 and rs2078267) resulted in moderate decrease of torsemide renal clearance, while the SNP (rs4930423) led to an increased clearance of such drug. Ogasawara et al [57] also discovered one same mutation (-18C>T) from the Japanese cohort, which study concluded that it did not affect the promoter activity or the mRNA expression of this gene. Meanwhile, Lee et al [60] explored the functional consequence of E278K, which mutant possessed a reduced uptake activity of ES, Dehydroepiandrosteon sulfate (DHEA-s) and ochratoxin A (OTA).…”
Section: Oat4mentioning
confidence: 93%
“…In the study of 50 Korean human subjects, an additional synonymous SNP (1539G>A) and three more intronic SNPs (i4+269G>A, i7+154T>C and i9+206A>G), were recently reported [52]. However, Ogasawara et al [57] observed no polymorphism in the promoter region of OAT2, with 63 kidney samples from Japanese.…”
Section: Oat2mentioning
confidence: 99%
See 1 more Smart Citation
“…У кількох дослідженнях вказується на те, що ген SLC22A2 є ви-сокополіморфним за своєю природою [40][41][42][43]. Zolk et al [44] виявили, що такий варіант гена SLC22A2, як 808G > T (270Ala > Ser), сприяє зниженню біо-трансформації ліків.…”
Section: Solute Carrier Family 22 Memberunclassified
“…Ogasawara изучал регуляторные полиморфизмы в транспортерах и обнару-жил в ОСТ2 делецию в промоторной зоне (578-576delAAG). Было показано, что при наличии этого полиморфизма уменьшался уровень экспрессии мРНК ОСТ2 [23].…”
Section: полиморфизмы ост2unclassified